Structure and composition of the phytoplanktonic community in TRanca Grande Lagoo (Junín, Perú) - Mariano-Astocóndor, Mauro (2001)
The Tranca Grande lagoon is one of the systems where the truchiculture is realized, a productive activity which supports the lake since 1995. It is located in the Paramo floor or Tropical Montano in the Department of Junin, Province of Jauja to 4320 m of altitude (11º43’57?S) and (75º13’18? W). The structure and composition of the superficial phytoplanktonic community was studied from monthly samples collected from January to December on 1996 in relation to 21 physical-chemical variables of water. The community showed 51 species belonging to Bacillariophyta, Chlorophyta, Cyanophyta, Euglenophyta, Chrysophyta and Pyrrophyta. The highest average values of density were from Gloeocystis gigas and Ulothrix sp. On the rainy months, the rain fall had a considerable influence on the dilution and sedimentation of the macronutrients responsible for the conductivity, alkalinity, hardness, calcium and magnesium which decrease their values, and likewise the values of the diversity and density decrease. In the period of low-water mark, the characteristics mentioned about rainy period appear on the inverse way. The quantity of species and their density on the phytoplankton were found with the Multiple Regression Analysis. a) Species = 7,32+10,59 (The clearness of water)) - 0,1614 (hardness of calcium ) + 4,90 (nitrates). b) Density = -1,00 + 4397,18 (pH) - 223,6 (total alkalinity) - 1,4 (phosphates)